Pain as a presenting symptom of hypothyroidism - Nishant Kumar; Mrinal Kamal; Pramod Kohli (Wolters Kluwer Medknow Publications, 2024)
Chronic back or limb pain is often debilitating and disabling resulting in loss of efficiency, depression, and low self-esteem. Diagnosis usually suggests arthritis or nerve root pathology and patients receive long-term oral analgesics and invasive procedures with little or no relief. Hypothyroidism may present as peripheral neuropathy which may be clinically indistinguishable from entrapment neuropathy as occurs with neural canal stenosis. Muscle cramps, aches, proximal symmetrical muscle weakness, stiffness, polymyositis, and exercise intolerance may be the only presenting symptom indicating hypothyroidism. We present five cases of acute on chronic pain that improved significantly on treatment with thyroxine. Neuromuscular pain may be the only presenting symptom of hypothyroidism. Thyroid profile (TSH, FT3, FT4) and anti-thyroid peroxidase (anti-TPO) antibodies should be screened before subjecting the patient to multiple analgesics and procedures.